Covid-19, and the Educational System of Pakistan An Assessment - Hassan, Muhammad; Rizwan, Muhammad (University of Wah Journal of Social Sciences, 2022)
This research regarding the impacts of Covid-19 on education sector of Pakistan analyses the situation resulted in the wake of officially declared pandemic by the World Health Organization. Like most of the countries, Pakistan faced serious repercussions in this regard; trade, industry, health and tourism have badly affected; however, unbearable loss to the education sector has almost shaken the country. This paper strives to highlight that how every sector especially education in Pakistan has been severely paralyzed by activities related to the coronavirus. Yet every possible effort has been made by the authorities to prevent the disruption of education by using online system of classes with the use of various apps including Zoom, Microsoft Team and WhatsApp etc. The adoption of Learning Management System (LMS), use of hybrid classroom and broadcast on television have been new ideas to be adopted in the wake of this pandemic. This research pinpoints that how a developing country like Pakistan, generally appears to face a challenge due to non-availability of valid tool, system and skill that caused damage to the education system of the country. Main objective of the study is to analyse the challenges, worries and impacts of transition process from formal to digital education. This research has focussed on the impacts of this pandemic on education sector, which has already been facing lack of basic infrastructure including trained teaching staff and modern equipment for tangible results.